Zoon’s Balanitis – Update of Clinical Spectrum and Management - Vineet Relhan; Abhinav Kumar; Aneet Kaur (Indian Journal of Dermatology)
Zoon’s balanitis or balanitis plasmacellularis circumscripta is a chronic inflammatory disorder of the genital mucosa that can affect both males and females (Zoon’s vulvitis). It is not a sexually transmitted disease but can still cause anxiety to the patients because of its chronic nature. Hence, proper diagnosis and early management are necessary. It is a clinical mimicker of other commoner genital dermatoses and is mostly a diagnosis of exclusion when other diseases have been ruled out. It is characterised by a well-demarcated shiny erythematous patch or plaque over the genital mucosa. Histopathological examination becomes necessary when we are unable to differentiate it from premalignant lesions. It reveals lozenge-shaped keratinocytes with siderophages, haemorrhages and variable plasma cell infiltrate in the dermis. Dermoscopy shows spermatozoa-like, convoluted vessels with structureless red orange areas. Response to topical therapy alone is not always satisfactory. However, lasers and surgical management can provide long-term remission.